Health information professionals and the Semantic Web: a symbiotic relationship? - McArthur A (Journal of the Canadian Health Libraries Association (JCHLA))
Objective -- To identify opportunities for health information professionals to participate in the ongoing development of the Semantic Web and to investigate the benefits promised by emerging semantic technologies. Methods -- A search of two biomedical databases (MEDLINE, CINAHL), three information science databases (LISTA, LISA, and Library Literature), and Web-published literature retrieved articles on core Semantic Web concepts that relate to the practice of information professionals and the use of Semantic Web technologies in a health care context. Articles that focused solely on Semantic Web architecture and similar technology-focused literature were not selected for inclusion. A basic thematic analysis was performed to identify trends in the selected literature. Results -- Five key areas of professional focus emerged as themes: ontology development, knowledge translation, information retrieval, scientific publishing, and resource classification and indexing. Discussion -- Health information professionals have a role to play in the development of a powerful and nuanced biomedical Semantic Web. Rather than making traditional medical library positions obsolete, the Semantic Web could present new opportunities for information professionals within the five identified areas of professional focus. In turn, semantic technologies developed with the input of experienced health information professionals have the potential to transform the practice of these professionals, particularly within the five aforementioned areas.